2022
DOI: 10.1038/s41586-022-05272-1
|View full text |Cite
|
Sign up to set email alerts
|

LRRC15+ myofibroblasts dictate the stromal setpoint to suppress tumour immunity

Abstract: Recent single-cell studies of cancer in both mice and humans have identified the emergence of a myofibroblast population specifically marked by the highly restricted leucine-rich-repeat-containing protein 15 (LRRC15)1–3. However, the molecular signals that underlie the development of LRRC15+ cancer-associated fibroblasts (CAFs) and their direct impact on anti-tumour immunity are uncharacterized. Here in mouse models of pancreatic cancer, we provide in vivo genetic evidence that TGFβ receptor type 2 signalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(154 citation statements)
references
References 35 publications
(65 reference statements)
11
106
0
Order By: Relevance
“…5a ). In the rat glia cell line C6 LRRC15 is mildly regulated in response to proinflammatory cytokines like IL1β, IL6, and TNFɑ 27 , and more recently TGFβ signalling has been linked to LRRC15 expression in cancer-associated fibroblasts 28, 29 . In human fibroblasts, we found IL1β, TNFɑ or IFNɣ do not induce detectable levels of LRRC15 (not shown), however TGFβ upregulates both LRRC15 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5a ). In the rat glia cell line C6 LRRC15 is mildly regulated in response to proinflammatory cytokines like IL1β, IL6, and TNFɑ 27 , and more recently TGFβ signalling has been linked to LRRC15 expression in cancer-associated fibroblasts 28, 29 . In human fibroblasts, we found IL1β, TNFɑ or IFNɣ do not induce detectable levels of LRRC15 (not shown), however TGFβ upregulates both LRRC15 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, McAndrews et al recently showed that genetic depletion of FAP+ CAFs increased PDAC survival, while of αSMA+ CAFs decreased it [30]. Always using transgenic mice models, Krishnamurty and colleagues selectively depleted the LRRC15+ CAF subpopulation in PDAC, and this was sufficient to significantly slow tumor growth and restore CD8+ T cell functions, increasing response to immunotherapy [31]. Since LRRC15+ CAF formation depends on TGFβ receptor 2 signaling [21], this opens the attractive possibility to use of TGFβ inhibitors to overcome CAF-mediated resistance to cancer immunotherapy.…”
Section: Caf Depletionmentioning
confidence: 96%
“…Similarly, two distinct CAF populations with opposing roles in the progression and immune landscape were identified in PDAC, as, in this context, depletion of fibroblast activation protein (FAP)+ CAFs increased survival, while depletion of αSMA+ CAFs decreased survival [30]. Also the TGFβ-driven expression of the leucine-rich-repeat-containing protein 15 (LRRC15) in CAFs, characterizes a pro-tumorigenic CAF subpopulation, as the depletion of LRRC15+ CAFs in PDAC models slowed tumor growth and restored CD8+ T cell functions, increasing response to immunotherapy [31]. Why CAFs are so heterogeneous is not clear.…”
Section: Background: Being Cafsmentioning
confidence: 99%
See 2 more Smart Citations